Mirna and Jessica Case on Jakarta Post; Grammatical Cohesion Analysis (Discourse Approach) - Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2017)
Discourse used in linguistics refers to any passage, spoken or written. As the news about â€œMirna dan Jessica caseâ€ on Jakarta Post. Jakarta Post in one of the News Paper that published in Print out and on-line. In this research the researcher take the data from online news at July 2016. A text in the news include on a passage of discourse which is coherent in these two regards: it is coherent with respect to the context of situation and therefore consistent in register; and it is coherent with respect to itself, and therefore cohesion. This research analyzes the cohesion on the Mirna and Jessica case in Jakarta Post used descriptive design with qualitative method through Discourse approach. The result of the research on grammatical cohesion used in Jakarta post in the first news, are: promonimal reference â€œher, their, his, and theyâ€, the demonstrative reference â€œthe and thatâ€, Comparative Reference â€œasâ€, Cataphoric Reference â€œanotherâ€, Additive Conjunction â€œandâ€. For the second news are: Pronominal Reference â€œHer, she, you, they, theirâ€, Demonstrative Reference â€œtheâ€, Additive Conjunction â€œboth, andâ€, Adversative Conjunction â€œbutâ€